PENGEMBANGAN MODEL PEMBELAJARAN PROJECT CITIZEN BERBASIS PORTOFOLIO UNTUK KOMPETENSI PENDIDIK SOCIETY 5.0 - Helminsyah Helminsyah; Musdiani Musdiani; Ali Mustadi; Anwar Senen (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2022)
The learning model is an example for optimizing the teaching and learning process in the classroom, this study aims to determine the portfolio-based Project citizen learning model to strengthen the social competence of educators towards society 5.0. in the fourth-grade elementary school in Banda Aceh City. This research uses this research method, namely Research and development in the field of education (R & D) procedures and research steps for developing modifications of Borg & Gall, namely: (1) developing products, and (2) testing the effectiveness of products in achieving goals. This study focuses on testing the effectiveness of the learning model from the experimental and control class students' learning outcomes. The results of the study show that the test of the effectiveness of the use of the learning model is 85.00%, without the media is 75.90%. This is indicated by the results of the data tscore = 13.08, t table 0.05(2.49) = 1.67 then tscore (13.08) > ttable (1.67) for the significance level (α = 0.05) or with in other words, Ha is accepted and Ho is rejected. The test proves that the use of the Project citizen portfolio-based learning model to strengthen the social competence of educators towards society 5.0. more effective in improving student learning outcomes. The results showed: (1) the Thematic learning material expert test was in very good qualification (88.00%), (2) the learning design expert test was in very good qualification (87.76%), (3) the model expert test and learning graphics are in very good qualification (92.06%), (4) individual trials are in very good qualifications (89.88%), group trials are in very good qualifications (91.32%), field trials are in in very good qualification (89.96%). The product produced at the end of the development of this learning model is a portfolio-based project citizen to strengthen the social competence of educators towards society 5.0. followed by an effectiveness test. Abstrak Model Pembelajaran merupakan sebuah contoh untuk mengoptimalkan proses belajar mengajar dikelas, penelitian ini bertujuan untuk mengetahui model pembelajaran Project citizen berbasis portofolio untuk menguatkan kompetensi sosial pendidik untuk menuju society 5.0. di sekolah dasar Banda Aceh. Penelitian ini menggunakan metode penelitian ini adalah Riset dan pengembangan bidang pendidikan (R & D) prosedur dan Langkah- langkah penelitian pengembangan modifikasi Borg & Gall yaitu: (1) mengembangkan produk, dan (2) menguji keefektifan produk dalam mencapai tujuan. Penelitian ini fokus pada uji kefektifan model pembelajaran dari hasil belajar siswa kelas eksperimen dan kontrol. Hasil penelitian menujukkan bahwa uji efektifitas penggunaan model pembelajaran sebesar 85,00 %, tanpa media yaitu 75,90%. Hal ini ditunjukkan dengan hasil data thit = 13,08, ttabel0,05(2,49) = 1,67 maka th (13,08) > tt (1,67) untuk taraf signifikansi (α=0,05) atau dengan kata lain Ha diterima dan Ho ditolak. Dari uji membuktikan bahwa penggunaan model pembelajaran Project citizen berbasis portofolio untuk menguatkan kompetensi sosial pendidik untuk menuju society 5.0. lebih efektif dalam meningkatkan hasil belajar siswa. Hasil penelitian menunjukkan: (1) uji ahli materi pembelajaran Tematik berada pada kualifikasi sangat baik (88,00%), (2) uji ahli desain pembelajaran berada pada kualifikasi sangat baik (87,76%), (3) uji ahli ahli model dan kegrafisan pembelajaran berada pada kualifikasi sangat baik (92,06%), (4) uji coba perorangan berada pada kualifikasi sangat baik (89,88%), uji coba kelompokberada pada kualifikasi sangat baik (91,32%), uji coba lapanganberada pada kualifikasi sangat baik (89,96%). Produk yang dihasilkan pada akhir dari pengembangan model Pembelajaran ini Project citizen berbasis portofolio untuk menguatkan kompetensi sosial pendidik untuk menuju society 5.0. dilanjutkan dengan uji keefektifan.